Household and farm-level drivers of the use and intensity of soil fertility amendments in smallholder farming systems: a case of Masvingo District, Zimbabwe, and Mopani District, South Africa - Bombiti, Jean-Robert Nzanza; Taurayi, Silent; Mugari, Ephias; Tatsvarei, Simbarashe; Zvinavashe, Augustine Pontain; Musakwa, Walter (Frontiers in Agronomy, 2025)
IntroductionSmallholder farming systems critically secure livelihoods and significantly contribute towards household food security in Sub-Saharan Africa (SSA). Sustainable soil fertility management is, however, essential for improving crop and livestock productivity and resilience in smallholder farming systems.MethodsUsing the integrated soil fertility management (ISFM) approach, an investigation into the intricate relationship between socio-economic and farm-level factors and agricultural practices on the use and intensity of use of quantities of organic soil amendments (OSA) and inorganic soil amendments (ISA) among smallholder farmers in Masvingo, Zimbabwe and Mopani, South Africa, which remains poorly understood among rural farming communities, revealed complex relationships among these factors and issues.Results and discussionThe ISFM approach employing binary and ordered logistic regression models on household survey data (n=378) found that the farmer’s location (i.e. district), years of formal education, literacy, household labor, income sources and monthly income, total landholding, main crop grown, livestock ownership, soil type and soil testing significantly affected fertilizer adoption and fertilizer application intensity. Farmers in Masvingo, Zimbabwe, were more inclined to use and apply higher quantities of OSA and ISA than those in Mopani, South Africa, highlighting the role of regional agroecological and socio-economic differences. Cattle ownership significantly increased OSA use while negatively influencing ISA use, reinforcing the importance of crop-livestock integration. Additionally, soil testing encouraged ISA application but discouraged OSA use, suggesting that farmers perceived ISA as a more immediate response to soil fertility deficiencies.ConclusionThe contrasting influence of some socio-economic factors indicates the intricate nature of smallholder farming systems and how household characteristics are intertwined with ISFM decisions. Therefore, there is a need for context-specific farmer education programs, tailored soil testing programs, financial support for fertilizer access, and location-specific extension services to address the unique differences among smallholder farmers in rural areas to enhance soil fertility, improve crop and livestock productivity, and increase overall resilience in smallholder farming systems.